2008
DOI: 10.1007/s00384-008-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related genes variability in Czech patients with sporadic colorectal cancer: preliminary results

Abstract: The investigated single nucleotide polymorphisms within the genes encoding for obesity-related genes were observed to be associated both with clinical manifestation of colorectal cancer and with severity of the disease. Thus, we suggest that defined genetic variability in the genes might become DNA markers for colorectal cancer in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The association between LEP gene variants and CRC risk has been examined in several epidemiologic studies, and the results were conflicting ( 14 - 18 ). Our results are in line with studies by Slattery et al ( 14 ), Vasku et al ( 15 ), Pechlivanis et al ( 16 ) and by He and Xu ( 18 ), where no association was found between LEP gene rs7799039 variant and CRC risk; nevertheless, Partida-Perez et al ( 17 ) reported a significant association between other variants of this gene and CRC risk. The discrepancy in the reported associations between the LEP gene variants and CRC risk may be due to false positive results, small sample size, statistical methods, genotyped markers, population differences in allele frequencies, or differences in the dietary and lifestyle factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association between LEP gene variants and CRC risk has been examined in several epidemiologic studies, and the results were conflicting ( 14 - 18 ). Our results are in line with studies by Slattery et al ( 14 ), Vasku et al ( 15 ), Pechlivanis et al ( 16 ) and by He and Xu ( 18 ), where no association was found between LEP gene rs7799039 variant and CRC risk; nevertheless, Partida-Perez et al ( 17 ) reported a significant association between other variants of this gene and CRC risk. The discrepancy in the reported associations between the LEP gene variants and CRC risk may be due to false positive results, small sample size, statistical methods, genotyped markers, population differences in allele frequencies, or differences in the dietary and lifestyle factors.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we also analyzed the association between the rs1137101 (Gln223Arg) variant in the exon 6 of LEPR gene and CRC risk. Studies of the effect of LEPR gene variants on CRC risk have also been inconclusive ( 15 , 16 , 19 ). Consistent with our findings, Vasku et al ( 15 ), and Pechlivanis et al ( 16 ) found no association between LEPR gene rs1137101 variant and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that genetic variation in LEPR affected cancer susceptibility with significantly higher frequency of the LEPR 223Arg allele in patients than in controls [9,11,22,24,33]; however, this association was not be replicated by later studies [14,16,19,23,31,36]. Likewise, previous reports also demonstrated that LEP 2548AA was associated with an increased risk of cancer [12,13,20,21,33,34]; however, replication of this finding by others also failed as well [25,28,31]. …”
Section: Discussionmentioning
confidence: 96%
“…RCC risk in relation to genetic variants in AGT has not been previously studied; however, AGT has been linked with other cancers. Specifically, an increased risk of postmenopausal breast cancer was found in a Dutch population among homozygous carriers of the M allele of rs699 (M235T) (26); a significantly higher number of heterozygote carriers of rs5051 (À6G.A) were found among Czech men with colorectal cancer compared with healthy men of similar age (27), and an increased risk of H. pylori-related gastric cancer was observed in a Japanese population among carriers of the C allele of rs5050 (À20A.C) (28). Rs699 is located in exon 2 and encodes a methionine to threonine amino acid change, and rs5051 and rs5050 are both located in the promoter (Figure 1).…”
Section: Gandreotti Et Almentioning
confidence: 99%